Method for producing crosslinkable biopolymers

JP2024509177A5Inactive Publication Date: 2025-02-13CELLCRAFT LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023553519
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-03-02
Filing Date
2022-03-01
Publication Date
2025-02-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Current methods for producing crosslinkable biopolymers, such as gelatin, alginate, and hyaluronic acid, are lengthy and inefficient, requiring dialysis for purification, which results in low yields, foam-like structures, and significant storage space requirements, while also being limited in scalability and reproducibility.

Method used

A method involving chemical modification with carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds, followed by precipitation in an organic solvent, significantly reduces processing time and produces biopolymers in particulate form that can be easily stored and handled, with improved mechanical strength.

Benefits of technology

The new method produces biopolymers with superior mechanical strength and reduces processing time by up to 86%, allowing for scalable and efficient production of compact, easily handled particles, while maintaining biocompatibility for tissue engineering applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000020_0000
    Figure 00000020_0000
  • Figure 00000020_0001
    Figure 00000020_0001
  • Figure 00000020_0002
    Figure 00000020_0002
Patent Text Reader

Abstract

The present invention relates to a method for producing a biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond, which comprises, following chemical modification in an aqueous solution, precipitating the biopolymer in an organic solvent, filtering and drying, and recovering the organic solvent by distillation. Also provided are biopolymers chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond, and hydrogels thereof obtained by said method.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THEINVENTION The present application relates to the technical field of crosslinkable biopolymers and methods for producing crosslinkable biopolymers, such as crosslinked proteins and crosslinked polysaccharides, on an industrial scale. [Background technology]

[0002] 2. Background of the Invention The search for a base biomaterial for tissue engineering and regenerative medicine applications requires that the biomaterial possess the following intrinsic properties: biocompatibility, degradability by enzymes naturally secreted by cells in culture, tunable physical and chemical properties, and of course, economical and reproducible manufacturing methods. Modified crosslinkable biopolymers (i.e., biopolymers modified with functional groups that make them crosslinkable) exhibit these intrinsic properties and have been widely used by many researchers to culture large numbers of cells. Following chemical modification with chemical modifiers that make them crosslinkable, the following biopolymers are commonly used as biosubstrates for bioprinting applications, which are the base inks loaded with cells: gelatin, alginate, hyaluronic acid, chitosan, chondroitin sulfate, collagen, and silk fibroin.

[0003] The currently used method for producing crosslinkable biopolymers relies on the use of dialysis as a purification method for the crosslinkable biopolymers. Specifically, after the reaction is complete, the reaction product of the biopolymer chemical modification is poured onto a membrane and suspended in water for several days at a constant temperature. The crosslinkable biopolymers are retained in the membrane, whereas the unwanted reaction products, such as unreacted chemical modifiers, their by-products, and buffer salts, diffuse out of the membrane when suspended in water. Subsequent daily water exchanges purify the crosslinkable biopolymers inside the membrane, leaving only the crosslinkable biopolymers dissolved in water. The water is finally removed by freeze-drying the solution, leaving a foam-like structure after processing, as shown in Figure 2a. Depending on the water content of the crosslinkable biopolymers after dialysis, dialysis usually takes 7 days and freeze-drying takes 4-7 days (Nichol et al., Biomaterials 31 (2010) pp. 5536-5544). Thus, the currently available methods for producing crosslinkable biopolymers involve a total purification time of about 11-14 days. During this manufacturing process, low and large volumes of crosslinkable biopolymer are processed and purification is limited to a few grams of dried crosslinkable biopolymer. The resulting crosslinkable biopolymer is in foam form and requires a large storage space.

[0004] Because currently used methods for producing crosslinkable biopolymers that rely on the use of dialysis as a purification method are lengthy (multi-day processing time limits), provide only limited quantities of crosslinkable biopolymers in foam form, and suffer from reproducibility, there is an unmet need to provide a convenient, reproducible, and environmentally friendly method for producing crosslinkable biopolymers, preferably as particles that can be easily stored and handled. Summary of the Invention [Problem to be solved by the invention]

[0005] Summary of the Invention It is therefore an object of the present invention to provide an advantageous, scalable and environmentally friendly method for the preparation of biopolymers chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds and nitrogen-nitrogen triple bonds. This object is achieved by the method according to claim 1. [Means for solving the problem]

[0006] Also claimed and described herein is a biopolymer, preferably in the form of particles, chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds, obtained by the method of preparation claimed and described herein.The particles claimed and described herein can be stored in a significantly smaller space than known cross-linked biopolymers purified via dialysis.Furthermore, the chemically modified biopolymers obtained by the method of preparation claimed and described herein show mechanical strength properties superior to known cross-linked biopolymers purified via dialysis.

[0007] A further aspect of the present invention is directed to a hydrogel as claimed and described herein obtained from a biopolymer chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds. [Brief description of the drawings]

[0008] [Figure 1] 1 shows a process flow diagram of an industrial production method according to the present invention. [Diagram 2] Shown are photomicrographs (left) and scanning electron micrographs (center and right) of dialyzed (top) and precipitated (bottom) gelatin methacrylate. [Diagram 3] Representative thermogravimetric curves of (left) dialyzed and (right) precipitated gelatin methacrylate are shown, with the X-axis being % weight and the Y-axis being temperature (° C.). [Figure 4]Chromatograms (left column) and molecular weight distributions (right column) of dialyzed (top) and precipitated (bottom) gelatin methacrylate using gel permeation chromatography. The x-axis of the chromatograms (left column) is elution time. Left column: left y-axis is mV, right y-axis is logMW. Student's t-test shows significant differences between number average molecular weight (Mn) and weighted averaged molecular weight (Mw) (***p<0.0001, n=3); y-axis is molecular weight. The calculated polydispersities of dialyzed gelatin methacrylate (first and second bars) and precipitated gelatin methacrylate (third and fourth bars) were 1.85±0.024 and 2.35±0.016, respectively. Error bars represent standard deviation (SD). [Diagram 5] (Top panel): Gelatin methacrylate hydrogels (from left to right): 5% dialyzed gelatin methacrylate, 5% precipitated gelatin methacrylate, 10% dialyzed gelatin methacrylate, and 10% precipitated gelatin methacrylate. (Bottom left) Compressive modulus on y-axis (Young's modulus, kPa), x-axis, from the left, 1st bar 5% dialyzed gelatin methacrylate, 2nd bar 5% precipitated gelatin methacrylate, 3rd bar 10% dialyzed gelatin methacrylate, and 4th bar 10% precipitated gelatin methacrylate; and (bottom right) swelling ratio of gelatin methacrylate hydrogels on y-axis (swelling ratio), x-axis, from the left, 1st bar 5% dialyzed gelatin methacrylate, 2nd bar 5% precipitated gelatin methacrylate, 3rd bar 10% dialyzed gelatin methacrylate, and 4th bar 10% precipitated gelatin methacrylate; Error bars are standard deviation. Different concentrations and downstream processing techniques show statistically significant differences by ANOVA and Tukey's post-hoc test (*p<0.05, **p<0.01, ***p<0.001, n≧3). Error bars represent standard deviation (SD). [Figure 6]Strain sweeps at 1 Hz and 37°C for (top left) 5% dialyzed, (top right) 5% precipitated, (bottom left) 10% dialyzed, and (bottom right) 10% precipitated gelatin methacrylate. The square dots are the storage modulus and the triangles are the loss modulus. The x-axis is strain (%) and the y-axis is G' and G'' (Pa). [Figure 7] Frequency sweeps at 0.5% strain and 37°C for (top left) 5% dialyzed, (top right) 5% precipitated, (centre left) 10% dialyzed and (centre right) 10% precipitated gelatin methacrylate. Square dots are storage modulus and triangles are loss modulus. X-axis is strain (%) and y-axis is G' and G'' (Pa). Bar graph of storage modulus (bottom left) and loss modulus (bottom right) determined for all samples, y-axis (bottom left) storage modulus and y-axis (bottom right) loss modulus, x-axis is 5% dialyzed gelatin methacrylate, 2nd bar is 5% precipitated gelatin methacrylate, 3rd bar is 10% dialyzed gelatin methacrylate and 4th bar is 10% precipitated gelatin methacrylate. Statistically significant differences with 95% CI by ANOVA and Tukey's post-hoc test between 5% dialyzed and precipitated gelatin methacrylate and 10% precipitated gelatin methacrylate (*p<0.05, **p<0.01, n>=3). Error bars represent standard deviation (SD). [Figure 8] Time sweeps at 1 Hz, 0.5% strain, and 37°C for (top left) 5% dialyzed gelatin methacrylate, (top right) 5% precipitated gelatin methacrylate, (bottom left) 10% dialyzed gelatin methacrylate, and (bottom right) 10% precipitated gelatin methacrylate are shown. The square dots are the storage modulus and the triangles are the loss modulus. The x-axis is time (s) and the y-axis is G' and G'' (Pa). [Figure 9]Temperature sweeps at 1 Hz, 0.5% strain, and a heating rate of 2°C / min are shown for (top left) 5% dialyzed gelatin methacrylate, (top right) 5% precipitated gelatin methacrylate, (bottom left) 10% dialyzed gelatin methacrylate, and (bottom right) 10% precipitated gelatin methacrylate. The square points are the storage modulus and the triangles are the loss modulus. The x-axis is temperature (°C) and the y-axis is G' and G'' (Pa). [Figure 10] (Top) Assessment of cell viability using Live (green, calcein AM)-Dead (red, ethidium homodimer) staining of NIH 3T3 fibroblasts encapsulated in 5% dialyzed and precipitated gelatin methacrylate (rows 1 and 2) and 10% dialyzed and precipitated gelatin methacrylate (rows 3 and 4) at days 1 (left) and 4 (right). (Bottom) Bar graphs show no significant differences in cell viability between days of culture (repeated measures ANOVA, p=0.1114, at least 50 cells in each of three different areas were analyzed). Error bars represent standard deviation (SD). X-axis: Left side parallel bars - day 1, from left to right: 1st bar 5% dialyzed gelatin methacrylate, 2nd bar 5% precipitated gelatin methacrylate, 3rd bar 10% dialyzed gelatin methacrylate, and 4th bar 10% precipitated gelatin methacrylate; Right side parallel bars - day 4, from left to right: 1st bar 5% dialyzed, 2nd bar 5% precipitated, 3rd bar 10% dialyzed, and 4th bar 10% precipitated gelatin methacrylate. Y-axis: Cell viability (%). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] Detailed Description of the Invention Addressing this need is therefore the subject of the present invention. This object is achieved by a manufacturing method as defined in claim 1, a biopolymer chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds and nitrogen-nitrogen triple bonds as defined in claim 14, and a hydrogel as defined in claim 15. Preferred embodiments are disclosed in the description and the dependent claims.

[0010] In the following the invention will be described in more detail.

[0011] Where the present description refers to "preferred" embodiments / features, to the extent that specific combinations of the "preferred" embodiments / features are technically meaningful, combinations of those "preferred" embodiments / features are also considered to be disclosed.

[0012] Unless otherwise specified, the following definitions shall apply herein.

[0013] As used herein, the terms "a," "an," "the," and similar terms used in the context of the present invention (particularly in the context of the claims) are to be construed to cover the plural as well as the singular, unless otherwise specified herein or clearly contradicted by context.

[0014] As used herein, the term "and / or" means that either all of the elements of the group or only one of them may be present. For example, "A and / or B" means "only A, or only B, or both A and B." In the case of "only A," the term also encompasses the possibility that B is absent, i.e., "only A and not B."

[0015] The terms "including," "containing," and "comprising" are used herein in their open-ended, non-limiting sense. It is understood that the various embodiments, options, and ranges are combinable at will. Thus, for example, a solution containing compound A may contain other compounds in addition to A. However, the term "comprising" also encompasses the more restrictive meanings of "consisting essentially of" and "consisting of," as a particular embodiment thereof, so that, for example, a "solution containing A, B, and optionally C" may further consist (essentially) of A and B, or consist (essentially) of A, B, and C. As used herein, the transitional phrase "consisting essentially of" (and grammatical variants) should be construed to include the recited materials or steps, as well as materials or steps that do not substantially affect the basic and novel characteristics of the claimed invention. Thus, the term "consisting essentially of" should not be construed as equivalent to "comprising."

[0016] The term "about" as used herein means that the amount or value in question may be the particular value specified or another value in its vicinity. In general, the term "about" referring to a particular value is intended to indicate a range within ±5% of that value. As an example, the expression "about 100" indicates a range of 100±5, i.e., a range of 95 to 105. Preferably, the range indicated by the term "about" indicates a range within ±3%, more preferably ±1% of the value. In general, when the term "about" is used, it is expected that similar results or effects according to the present invention can be obtained within a range of ±5% of the indicated value.

[0017] Surprisingly, the next step: (a) dissolving a biopolymer selected from proteins, polysaccharides, salts thereof, and mixtures thereof in an aqueous solution; (b) reacting the biopolymer with a chemical modifying agent containing a carbon-carbon double bond, a carbon-carbon triple bond, and / or a nitrogen-nitrogen triple bond to obtain a solution containing the biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond; (c) adding the solution obtained in step (c) to an organic solvent to obtain a suspension containing a precipitate of biopolymers chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds; (d) filtering the suspension obtained in step (c) to obtain a precipitate and a filtrate; (e) distilling the filtrate to recover the organic solvent; and (f) drying the precipitate to obtain a biopolymer chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds; It has been found that the method comprising: providing chemically modified biopolymers with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds that exhibit improved mechanical strength properties compared to known crosslinked biopolymers purified via dialysis, significantly shortening processing time due to the reduction in the time required for purification and drying of the chemically modified biopolymer, is scalable, and environmentally friendly. The manufacturing method claimed and described herein dramatically reduces the time required for purification and drying of the chemically modified biopolymer by using precipitation in organic solvents instead of dialysis as a purification method for the chemically modified biopolymer.

[0018] The term "biopolymer" as used herein relates to proteins, polysaccharides, protein salts, polysaccharide salts, or mixtures thereof. The biopolymers described herein contain at least one free amine group and / or hydroxyl and / or carboxylic acid groups present on the majority of their monomer units (amino acids, monosaccharides). The biopolymers described herein may be produced by living organisms or may be derivatives thereof. Thus, the biopolymers may be the same as those found in nature (i.e., natural biopolymers produced by living or previously living organisms, such as gelatin) or may be derivatives thereof (i.e., derived from natural biopolymers produced by living or previously living organisms, the derivation resulting from the synthetic method used to isolate the biopolymer from nature).

[0019] The terms "carbon-carbon double bond, carbon-carbon triple bond, and / or nitrogen-nitrogen triple bond containing chemical modifying agent", "chemical modifying agent" and "chemical modifier" are used interchangeably in this patent application and refer to a molecule or compound that includes one moiety that can react with amine and / or hydroxyl and / or carboxylic acid groups of a biopolymer and a second moiety that contains a carbon-carbon double bond (-C=C-), a carbon-carbon triple bond (-C≡C-), and / or a nitrogen-nitrogen triple bond (-N≡N-). As used herein, a "moiety" refers to a part of a molecule or compound that has a certain functional or structural characteristic. For example, a moiety can include a functional group or a reactive portion of a compound.

[0020] The term "biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond" as used herein refers to a biopolymer as described herein that has been reacted with a chemical modifying agent as described herein such that some of the free amine groups and / or hydroxyl and / or carboxylic acid groups present on the biopolymer are replaced with moieties containing a carbon-carbon double bond, a carbon-carbon triple bond, and / or a nitrogen-nitrogen triple bond. The expressions "chemically modified biopolymer" and "biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond" are used interchangeably in this patent application. The introduction of carbon-carbon double bonds, carbon-carbon triple bonds, and / or nitrogen-nitrogen triple bonds on biopolymers is particularly useful for crosslinking said biopolymers via methods well known in the art, such as thiol-ene reactions, thiol-yne reactions, and cycloadditions, including strain-promoted azide-alkyne cycloadditions and Diels-Alder cycloadditions. The term crosslinking, as used herein, refers to the covalent crosslinking of different portions of a biopolymer chemically modified with a functional group selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds, or the covalent crosslinking of different biopolymers, at least one of which is a biopolymer chemically modified with a functional group selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds, as described herein. Crosslinking involves reaction of carbon-carbon double bonds, carbon-carbon triple bonds, and / or nitrogen-nitrogen triple bonds present on a biopolymer chemically modified with a functional group selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds with suitable functional groups, such as thiol groups, azide groups, and double bonds.

[0021] A preferred embodiment of the present invention comprises a step (g) carried out after step (f): (g) subjecting the biopolymer obtained in step (f) to a size reduction process to prepare particles of said biopolymer. The particles prepared by the manufacturing methods claimed and described herein can be stored in a significantly smaller space and are easier to handle than known crosslinked biopolymers purified via dialysis.

[0022] Preferably, the process claimed and described herein further comprises a step (h) carried out after step (d): dissolving the precipitate in water to obtain a solution containing a biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond; adding the solution to an organic solvent to obtain a suspension containing a precipitate of a biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond; and filtering the suspension to obtain a precipitate and a filtrate. Preferably, step (h) is carried out at least twice. Preferably, step (h) is carried out at a temperature between room temperature and 60° C.

[0023] In step (a) of the manufacturing method claimed and described herein, the biopolymer described herein is dissolved in an aqueous solution. Depending on the solubility of the biopolymer to be dissolved, step (a) can be carried out at a temperature between room temperature and 60°C. For example, biopolymers such as polysaccharide salts and albumin can be dissolved in an aqueous solution at room temperature, and biopolymers such as gelatin can be dissolved in an aqueous solution at a temperature between about 40°C and about 60°C. Preferably, the concentration of the biopolymer in the aqueous solution is between about 1 wt% / vol and about 20 wt% / vol, preferably about 1 wt% / vol and about 10 wt% / vol.

[0024] The aqueous solution used in step (a) is preferably an acidic aqueous solution, a basic aqueous solution, or an aqueous buffer solution. Examples of suitable aqueous acid solutions include, but are not limited to, an aqueous acetic acid solution, preferably having a concentration of about 1-3 wt% / vol, an aqueous formic acid solution, preferably having a concentration of about 1-3 wt% / vol, and mixtures thereof. Examples of suitable aqueous basic solutions include, but are not limited to, an aqueous sodium hydroxide solution, preferably having a concentration of about 5-15 wt% / vol, an aqueous lithium hydroxide solution, preferably having a concentration of about 5-15 wt% / vol, and mixtures thereof. Examples of suitable aqueous buffer solutions include, but are not limited to, a carbonate-bicarbonate buffer, preferably 0.01-0.5 M carbonate-bicarbonate buffer, a phosphate buffer, a 2-(N-morpholino)ethanesulfonic acid (MES) buffer, a citrate buffer, a borate buffer, and mixtures thereof. The aqueous solution is preferably free of organic solvents.

[0025] In a preferred embodiment, the biopolymer is a protein or a salt thereof. Examples of suitable proteins include, but are not limited to, gelatin, collagen, elastin, silk fibroin, albumin, and mixtures thereof. Preferably, the protein is gelatin. When the biopolymer dissolved in step (a) is a protein or a salt thereof, step (b) of the manufacturing method claimed and described herein preferably comprises the following steps (b-1) to (b-4): (b-1) adjusting the pH of the solution obtained in step (a) to a value between about 2 and about 10; (b-2) adding a chemical modifying agent to the solution obtained in step (b-1); (b-3) stirring at a temperature between room temperature and 60° C. for about 0.5 to about 5 hours; and (b-4) preferably terminating the reaction by adjusting the pH of the solution to a value between about 6.5 and about 7.5. Contains:

[0026] Therefore, a preferred embodiment according to the present invention comprises the steps of: (a) dissolving the protein, its salt, or a mixture thereof in an aqueous solution as defined herein, preferably free of organic solvents; (b-1) adjusting the pH of the solution obtained in step (a) to a value between about 2 and about 10; (b-2) adding a chemical modifying agent to the solution obtained in step (b-1); (b-3) stirring at a temperature between room temperature and 60° C. for about 0.5 to about 5 hours; (b-4) preferably terminating the reaction by adjusting the pH of the solution to a value between about 6.5 and about 7.5; (c) adding the solution obtained in step (c) to an organic solvent to obtain a suspension containing a precipitate of proteins chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds; (d) filtering the suspension obtained in step (c) to obtain a precipitate and a filtrate; (e) distilling the filtrate to recover the organic solvent; (f) drying the precipitate to obtain a protein chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond; Optionally, step (g) subjecting the protein obtained in step (f) to a micronization process to prepare particles of said protein. The present invention relates to a method for producing a protein chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond, preferably a protein chemically modified at a carbon-carbon double bond, comprising the steps of: Preferably, the method further comprises step (h), which is preferably carried out at least twice.

[0027] It is within the general knowledge of a person skilled in the art to take into account the structure of the protein to be chemically modified and of the chemical modifying agent used, in order to adjust the pH of the solution to an appropriate value between about 2 and about 10 so that the hydroxyl and / or amino and / or carboxylic acid groups present on the protein react with the chemical modifying agent. For example, when using gelatin as the biopolymer to be modified, the pH of the solution should be adjusted to a value between about 7 and about 10 in step (b-1).

[0028] Preferably, in step (b-4), the reaction is stopped by adjusting the pH of the solution to a value between about 6.5 and about 7.5, which can be accomplished using a basic aqueous solution as described herein, an acidic aqueous solution as described herein, or an aqueous buffer solution as described herein.

[0029] In a further preferred embodiment, the biopolymer is a polysaccharide, or its salt. Examples of suitable polysaccharides include, but are not limited to, alginic acid, gellan gum, pectin, polygalacturonic acid, carrageenan, hyaluronic acid, chitosan, chondroitin sulfate, cellulose, carboxymethylcellulose, hydroxymethylcellulose, glycosaminoglycan, and mixtures thereof. The polysaccharide salt is preferably selected from polysaccharide sodium salt, polysaccharide potassium salt, polysaccharide ammonium salt, and mixtures thereof. In a further preferred embodiment, the biopolymer is preferably selected from polysaccharide salts, sodium alginate, sodium hyaluronate, sodium gellan gum, sodium pectinate, sodium polygalacturonate, sodium carrageenan, sodium chondroitin sulfate, and mixtures thereof, more preferably selected from sodium alginate, sodium hyaluronate, and mixtures thereof.

[0030] If the biopolymer dissolved in step (a) is a polysaccharide or a salt thereof, step (b) of the process claimed and described herein preferably comprises the following steps (b-5) and (b-6): (b-5) adding a chemical modifying agent to the solution obtained in step (a); and (b-6) stirring for at least 3 hours, preferably at least 8 hours, more preferably at least 12 hours, such as 24 hours, preferably at room temperature; Thus, a preferred embodiment according to the present invention comprises the steps of: (a) dissolving the polysaccharide, its salt, or a mixture thereof in an aqueous solution as defined herein, preferably free of organic solvents; (b-5) adding a chemical modifying agent to the solution obtained in step (a); (b-6) stirring for at least 3 hours, preferably at least 8 hours, more preferably at least 12 hours, such as, for example, 24 hours, preferably at room temperature; (c) adding the solution obtained in step (c) to an organic solvent to obtain a suspension containing a precipitate of polysaccharides chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds; (d) filtering the suspension obtained in step (c) to obtain a precipitate and a filtrate; (e) distilling the filtrate to recover the organic solvent; (f) drying the precipitate to obtain polysaccharides chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds; Optionally, (g) subjecting the polysaccharide obtained in step (f) to a micronization process to prepare particles of said polysaccharide; The present invention relates to a method for producing a polysaccharide chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond, preferably a polysaccharide chemically modified with a carbon-carbon double bond, comprising the steps of: Preferably, the method further comprises step (h), which is preferably carried out at least twice.

[0031] In a preferred embodiment, the biopolymers dissolved in step (a) comprise at least two biopolymers, for example at least two different proteins, at least two different polysaccharides, or a mixture of proteins and polysaccharides.

[0032] In step (b) of the method of manufacture claimed and described herein, the biopolymer is reacted with a chemical modifying agent such that some of the free amine groups, and / or hydroxyl and / or carboxylic acid groups present on the biopolymer are replaced with moieties containing carbon-carbon double bonds, carbon-carbon triple bonds, and / or nitrogen-nitrogen triple bonds. As used herein, the term "chemical modifying agent containing carbon-carbon double bonds, carbon-carbon triple bonds, and / or nitrogen-nitrogen triple bonds" refers to a molecule or compound that contains one moiety that can react with the amine and / or hydroxyl and / or carboxylic acid groups of the biopolymer and a second moiety that contains carbon-carbon double bonds, carbon-carbon triple bonds, and / or nitrogen-nitrogen triple bonds. The terms "chemical modifying agent containing carbon-carbon double bonds, carbon-carbon triple bonds, and / or nitrogen-nitrogen triple bonds", "chemical modifying agent", and "chemical modifier" are used interchangeably in this patent application. As used herein, "moiety" refers to a part of a molecule or compound that has a certain functional or structural feature. For example, the moiety may include a functional group or reactive portion of a compound. Preferably, the chemical modifier is selected from (meth)acrylic anhydride, glycidyl (meth)acrylate, carbic anhydride, dibenzocyclooctyne-N-hydroxysuccinimidyl ester, dibenzocyclooctyne-amine, (1R,8S,9s)-bicyclo[6.1.0]non-4-yn-9-ylmethanol, and mixtures thereof. More preferably, the chemical modifier is selected from (meth)acrylic anhydride, glycidyl (meth)acrylate, carbic anhydride, and mixtures thereof.

[0033] In step (c) of the process claimed and described herein, the solution obtained in step (c) is added to an organic solvent to form a suspension containing a precipitate of biopolymers chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds. The organic solvent is preferably selected from alcohols, such as C1-C4 alcohols, alcohol-containing compositions, such as C1-C4 alcohol-containing compositions, ketones, esters, ethers, chloroform, and mixtures thereof. Examples of C1-C4 alcohols include methanol, ethanol, propanol, isopropanol, butanol, isobutanol, and tert-butanol. Examples of suitable ketones include acetone and methyl ethyl ketone. Examples of suitable esters include ethyl acetate. The organic solvent is more preferably selected from alcohols as defined herein, alcohol-containing compositions as defined herein, and ketones as defined herein, more preferably selected from ethanol, propanol and isopropanol, methanol denatured alcohol (industrial denatured alcohol, denatured alcohol), acetone, methyl ethyl ketone, and mixtures thereof. In the most preferred embodiment, the organic solvent is selected from ethanol and denatured alcohol. Step (c) is preferably carried out at room temperature. It is further preferred that the volume of the organic solvent is at least 3 times, more preferably at least 8 times, and more preferably 10 times, more than the volume of the solution containing the biopolymer chemically modified with a functional group selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds.

[0034] The resulting suspension is filtered to separate a precipitate of biopolymers chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds from a filtrate, which is further distilled to recycle the organic solvent used in the precipitation of biopolymers chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds, which organic solvent is reused in further precipitation steps.

[0035] In step (f) of the method of manufacture claimed and described herein, the precipitate of the biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond is dried to prepare a biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond. The drying method used in step (f) is preferably selected from tray drying, freeze drying, conveyor drying, rotary drum drying, vacuum drying, and combinations thereof, more preferably freeze drying.

[0036] In step (g) of the manufacturing method claimed and described herein, the biopolymer obtained in step (f) is subjected to a micronization method in order to prepare particles of said biopolymer, which are particularly advantageous for storage (small storage space compared to manufacturing methods using dialysis as a purification method) and handling. Preferably, the micronization method is selected from grinding, crushing, milling, and combinations thereof.

[0037] The second aspect of the present invention is directed to a biopolymer, preferably a particle, chemically modified with a functional group selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds, preferably a carbon-carbon double bond, obtained by the method claimed and described herein.The particles claimed and described herein can be stored in a significantly smaller space than known crosslinked biopolymers purified via dialysis.Furthermore, the biopolymers claimed and described herein show mechanical strength properties superior to known chemically modified biopolymers purified via dialysis.

[0038] A third aspect of the present invention provides a method for producing a method comprising the steps of: i) dissolving a biopolymer as claimed and described herein in a solution, and optionally adding a radical initiator to said solution; and ii) crosslinking the modified biopolymer with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds. The present invention relates to a hydrogel obtainable by a method comprising the steps of:

[0039] Preferably, the solution used in step i) is selected from phosphate buffer, RPMI 1640 medium (commercially available from Sigma Aldrich), Ham's F-10 nutrient mixture (commercially available from ThermoFischer), Ham's F-12 nutrient mixture (commercially available from ThermoFischer), Minimum Essential Medium (MEM) (commercially available from ThermoFischer), alpha modified Eagle's medium (a-MEM) (commercially available from ThermoFischer), and Dulbecco's modified Eagle's medium (DMEM) (commercially available from ThermoFischer). Depending on the nature of the biopolymer chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds, step i) may be carried out at a temperature between room temperature and 60° C. A radical initiator, such as a thermal radical initiator (e.g., ammonium persulfate) or a radical photoinitiator (e.g., Irgacure 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, commercially available from Sigma Aldrich), lithium phenyl-2,4,6-trimethylbenzoylphosphinate), and / or further biopolymers, and / or cells, such as primary cells (mesenchymal stem cells, smooth muscle cells, adipocytes), or cell lines (e.g., 3T3 cells, HeLa cells, induced pluripotent stem cells (iPS cells)), may be added in step i) to the solution containing the biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond. Preferably, the solution obtained in step i) has a pH value between about 6.5 and about 7.5. In step ii) the biopolymer is crosslinked by heating the solution or by irradiating the solution with UV-Vis light or by irradiation with an electron beam.

[0040] The method for producing the hydrogel further includes steps iii) and iv): iii) washing the hydrogel obtained in step ii) with a solution; iv) hydrating the hydrogel obtained in step iii). may include:

[0041] Preferably, the solution used in step iii) is selected from phosphate buffer, RPMI 1640 medium, Ham's F-10 nutrient mixture, Ham's F-12 nutrient mixture, Minimum Essential Medium (MEM), alpha modified Eagle's medium (a-MEM), and Dulbecco's modified Eagle's medium (DMEM).

[0042] The hydrogel may be obtained as microparticles. EXAMPLES

[0043] The following examples are provided to further illustrate the present invention, and are not intended to limit the scope of the invention.

[0044] One particular method for preparing modified crosslinkable biopolymers (i.e., biopolymers chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds) is outlined below and summarized in FIG. 1. A biopolymer is prepared at 1-20% wt / vol by dissolving the biopolymer in a solvent or buffer (M-01). pH adjustment may be necessary to obtain optimal reaction conditions. After dissolution of the biopolymer, a chemical modifier (i.e., methacrylic anhydride, glycidyl methacrylate, carboxylic anhydride, etc.) is added (R-01). After the reaction, the process can be stopped by pH modification by addition of acid or base (M-02). It is worth mentioning that M-01, R-01, and M-02 can be performed in the same vessel or in series for a continuous process. The reaction solution is then easily precipitated by adding the solution in a large volume of solvent (S-01, using volume of precipitation solvent: 8-10x volume of reaction solution). The precipitate can be removed from the solvent by filtration (F-01) and is soluble in deionized water above 40°C (M-03). The resulting solution is precipitated again and the process is repeated 3x to ensure complete removal of unwanted by-products and unreacted components of the reaction. The filtrate, which contains a large amount of solvent, can be recovered using distillation (B-01) for reuse in the precipitation step. The precipitated modified biopolymer is filtered to remove remaining excess solvent and then vacuum-dried or freeze-dried (D-01). The resulting product is a solid mass that can be dried and comminuted, after which the modified biopolymer is stored at room temperature or in a freezer at -20°C until use.

[0045] Example 1. Preparation and characterization of gelatin methacrylate (GelMA) Gelatin was prepared at 10% wt / vol by dissolving it in 0.25 M carbonate-bicarbonate buffer at 60 °C and 700 rpm. Once completely dissolved, the pH of the solution was adjusted to 9.0 using 5.0 N NaOH as suggested by the work of Shirahama et al., Synthesis. Sci Rep 6, 31036 (2016). Methacrylic anhydride was added slowly at a rate of 0.2 mL / gram (gelatin) while stirring. The reaction was maintained in a narrow-mouth reaction vessel covered with aluminum foil in light-free conditions and with minimal air pick-up. After 2 h of stirring at 60 °C, the reaction was stopped by cooling the reaction mixture to room temperature and then neutralizing the solution to pH 7.4 by adding 5.0 N NaOH or 1 M NaHCO3. The reaction products are worked up either via conventional dialysis (Method B) or precipitation (Method A) methods, which are discussed in the following sections.

[0046] A.) Downstream processing by precipitation of gelatin methacrylate (GelMA) The reaction solution was easily precipitated by dropping the solution into a large volume of denatured alcohol (volume of precipitation solvent: 10x volume of reaction solution). The precipitate was removed from the solvent via filtration and centrifugation and dissolved in deionized water at 60°C and 700 rpm. The resulting solution was precipitated again and the process was repeated 3x to ensure complete removal of unwanted by-products and unreacted components of the reaction. The precipitated GelMA was squeezed to remove the remaining excess solvent and then freeze-dried at -50°C for 24h. The resulting product was a solid mass, which was then ground using coffee grinds and stored in a -20°C freezer until use. This is referred to as Precipitated GelMA (PR).

[0047] B. Downstream processing of gelatin methacrylate (GelMA) by commonly used dialysis methods The effluent from the reactor was transferred to a dialysis bag with a molecular weight cutoff (MWCO) value of 12-14 kDa and suspended in a stirred tank containing deionized water at 40°C for 7 days. The dialysis process was also kept in an environment without light and with minimal air intake, and the dialysis water was changed daily. To obtain GelMA in anhydrous conditions, the dialyzed GelMA solution was snap-frozen by immersion in liquid nitrogen and lyophilized at -50°C for 7 days to remove excess water. The resulting product was a white foam GelMA, which was then stored in a freezer at -20°C until use. This product is called dialyzed GelMA (DI).

[0048] C. Characterization of Synthetic GelMA Morphological analysis The synthesized GelMA was imaged using an environmental scanning electron microscope (ESEM, FEI Quanta 650) in high vacuum mode. The dried sample was mounted on an aluminum stub with a carbon tab to fix the sample. The accelerating voltage used was 10 kV, and imaging included at least three different positions as representative images of the synthesized GelMA using several magnification modes.

[0049] Degree of substitution assay The TNBS method was used to determine the degree of methacrylation in gelatin. Briefly, 15 mg of sample was dissolved in 2 mL of 4% wt / vol NaHCO3 containing 0.01 M TNBS and reacted for 3 h at 40° C. and 125 rpm. 3 mL of 6.0 N HCl was added to the solution, the temperature was raised to T=80° C., and left to react for 1 h. The reaction vial was then immersed in a water bath to cool the solution to room temperature, and the solution was further diluted by adding 5 mL of distilled water. The absorbance was then measured at 345 nm using a 96-well plate reader (Infinite Pro, Tecan), and the degree of substitution (DS) was calculated from three independent triplicate samples as follows:

[0050]

number

[0051] Molecular weight distribution by gel permeation chromatography Gel permeation chromatography was used to analyze the molecular weight distribution of GelMA. A solution was prepared by dissolving gelatin methacrylate in tissue culture water at a concentration of 2.5 mg / mL. Aqueous GPC was performed using a Shimadzu UPLC system fitted with a RID-10A refractive index detector. The eluent was DPBS, used at a flow rate of 1 mL / min at 35°C. The instrument was equipped with three PL Aquagel-OH columns. PEG / PEO standards (EasiVial) were used for column calibration. Number and weighted average molecular weights and polydispersity of precipitated and dialyzed GelMA were then calculated from the chromatographic data.

[0052] thermogravimetric analysis GelMA DI and GelMA PR samples were analyzed using thermogravimetric analysis to determine the solids content consisting of inorganic salts from the buffer and gelatin. One gram of each sample was placed in a metal pan and then heated in a Mettler thermal analyzer from ambient temperature to 1000°C at a heating rate of 20°C / min in a 99.5% oxygen atmosphere. The weight loss and temperature traces were analyzed using the Mettler thermal analyzer software, and the inorganic salts remaining at 1000°C were determined from the % mass at the endpoint.

[0053] Example 2. Preparation and characterization of GelMA hydrogels Dissolution medium was prepared by premixing DMEM (Dulbecco's Modified Eagle Medium, purchased from Sigma Aldrich) with Irgacure 2959 (2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone, purchased from Sigma Aldrich) at a concentration of 0.5% wt / vol and leaving the mixed solution in an incubator overnight. 5% or 10% wt / vol of the synthesized GelMA was then dissolved in DMEM containing photoinitiator by magnetic stirring at T=50°C and 700 rpm. After complete dissolution, the solution was immersed in a water bath for 10 min to cool to room temperature, and then its pH was adjusted to about 7.4 using 1.0 M HCl. The cooled and pH-adjusted solution was pipetted into a cylindrical Teflon mold (φ=12 mm) in a volume of 250 μL and irradiated with a 15 W UV lamp at a wavelength of 365 nm for 5 min. The crosslinked GelMA hydrogels were then washed 3x with PBS to remove traces of photoinitiator and then immersed in 3 mL of DMEM containing antibiotic / antimycotic solution for 24 h in an incubator at 37 °C and 5% CO2 to ensure complete hydration of the samples.

[0054] Characterization of GelMA hydrogels Determination of compression modulus To determine the compressive modulus of the swollen hydrogels, samples were removed from the culture medium, the residual liquid was blotted using tissue paper, and the dimensions were measured using a vernier caliper. The hydrogels were then placed on a texture analyzer (Stable Microsystems) with a 32 mm probe diameter and a 5 kg load cell. A ramp displacement rate of 0.05 mm / s and 100% strain were used for mechanical property testing, and the compressive modulus was calculated over the linear region within the 0-10% strain range. From one set of synthetic GelMA, two independent experiments were performed in triplicate.

[0055] Rheological Analysis Rheological measurements of GelMA hydrogels were performed using a Physica MCR 301 rheometer (Anton Paar, UK). Cylindrical hydrated GelMA hydrogel samples of 25 mm were cut and mounted in the rheometer with a gap distance of 1 mm and a plate diameter of 25 mm. Strain sweep tests analyzed the storage modulus (G') and loss modulus (G'') from 0.1 to 100% at a constant frequency of 1 Hz and temperature T = 37 °C; time sweep tests were performed at a constant frequency rate of 1 Hz, 0.5% strain, and T = 37 °C for 300 s. The temperature sweep test range was 25 to 50 °C at a heating rate of 2 °C / min at a constant frequency rate of 1 Hz and 0.5% strain. From one set of synthesized GelMA, two independent experiments were performed in triplicate.

[0056] Swelling ratio evaluation Similar to the preparation of hydrogels for compressive modulus determination, crosslinked GelMA hydrogels were immersed in 3 mL of DMEM in a 6-well plate for 24 h in an incubator. The swollen hydrogels were then harvested, excess water removed, and weighed in a bijou vial. The hydrogels were then snap-frozen by immersion in liquid nitrogen and lyophilized at -50°C for 3 days to ensure complete removal of water. The weights of the lyophilized hydrogels were recorded in triplicate, and the swelling ratio was calculated as follows:

[0057]

number

[0058] cell culture An established laboratory cell line, NIH 3T3, was obtained and cultured in T75 flasks using DMEM containing 10% fetal bovine serum, 1% L-glutamine, and 1% antibiotic / antimycotic stock solution. Cells were passaged every 3 days at 80-90% confluence, aspirating the medium from the flask, washing with PBS, trypsinizing for 5 min, and stopping the reaction by adding culture medium in a 1:5 ratio (1 part trypsin in 5 parts culture medium), centrifuging at 200g for 5 min, and resuspending in a volume of 1 mL of medium. The passage ratio was maintained at 1:4, and the passage numbers used in the experiments were 44-46.

[0059] Cell viability assay 5-10% wt / vol GelMA was mixed in DMEM containing 0.5% wt / vol Irgacure 2959 and kept in an incubator for 5h with stirring using a tube roller. After complete dissolution, the solution was filter sterilized using a 0.2μm syringe filter in a cell culture hood and kept in the incubator overnight. NIH 3T3 cells were then trypsinized and then cultured at approximately 2x10 6 The cells were suspended in GelMA solution at a concentration of 1000 cells / mL, and 10 μL of the cell suspension was pipetted into a 24-well plate. The solution was then exposed to an Omnicure S2000 UV lamp with a wavelength of 320–500 nm and 6.9 mW / cm 2 After exposure to light at an intensity of 1000 x g for 15 s, crosslinked GelMA hydrogels were maintained in DMEM supplemented with 10% fetal bovine serum and 5% antibiotic / antimycotic stock solution for 4 days. Cell viability was quantified on days 1 and 4 using a calcein AM / ethidium homodimer Live-Dead staining kit (Invitrogen) according to the manufacturer's instructions.

[0060] statistical analysis The results of the experiments were statistically analyzed using one-way ANOVA with a statistical significance criterion of p<0.05. Tukey's post-hoc test was performed to identify differences in mean values. At least triplicate samples and more than 50 cells were analyzed, and all error bars represent standard deviation. GraphPad Prism 7.0.3 was used to perform all statistical calculations.

[0061] result The morphology of the products of dialysis and precipitation methods is clearly different from that of powders, from sheet-like structures. Precipitation gives a dense product that can be easily stored in small containers, whereas dialyzed GelMA requires spacious storage conditions. After the reaction process, the traditional way to purify GelMA is to use dialysis, where the reaction product is poured onto a membrane and suspended in water for several days at a constant temperature. Unwanted reaction products, such as methacrylic acid and unreacted methacrylic anhydride, together with the buffer salts used, begin to diffuse out of the membrane when suspended in water, whereas GelMA is retained in the membrane. Daily water exchange purifies the sample inside the membrane, leaving only GelMA dissolved in water. The water is finally removed by freeze-drying the solution, leaving a foam-like structure after processing (Figure 2a). Depending on the water content of the product after dialysis, dialysis usually takes 7 days and lyophilization 4-7 days (Nichol et al., Biomaterials 31 (2010) pp. 5536-5544), with a total purification time of about 11-14 days. With this method, low content and large volumes of solids are processed, and purification is limited to a few grams of lyophilized GelMA.

[0062] In the precipitation method, separation of the unwanted reaction products and GelMA occurs immediately due to phase separation. When the reaction products are slowly poured into a large amount of alcohol, e.g., IMS (industrial methylated solvent) or ethanol, methacrylic acid and methacrylic anhydride diffuse into the alcohol due to their high solubility, whereas GelMA is insoluble in alcohol and precipitates. As suggested by the evaluation of the solids content using thermogravimetric analysis (Figure 3), the buffer salts used in the reaction were likely removed (by suspension in alcohol), and there was no significant difference between the salt content of dialyzed GelMA (7.07 ± 0.28%) and that of precipitated GelMA (7.18 ± 0.59%) (p = 0.8328, n = 2). Unwanted reaction products may co-precipitate with precipitated GelMA, so redissolution in water followed by precipitation may ensure significant removal of those by-products. Precipitated GelMA can be removed from the alcohol suspension by filtration and centrifugation, leaving a compact solid mass, and the remaining solvent is easily removed by vacuum or lyophilization (Figure 2b). The process time for precipitation takes only a few hours, with drying of the solids accounting for the majority of the process time (12-24 h). The produced product is compact and powdery, requiring less storage volume, improving handling compared to the dialyzed product of GelMA purification and reducing a significant portion of the overall process time. The method is also easily scalable, and the solvent (alcohol) can be recovered by distillation for reuse, improving overall economics. The substitution degree of the synthesized GelMA was 97.77% and 93.28% by dialysis and precipitation methods, respectively (n=3, 4 replicates), and the substitution degree of both DI GelMA and PR GelMA does not show significant differences (t-test, p=0.0623).

[0063] Molecular weight of GelMA The molecular weight of porcine gelatin with 175-225 bloom published by the manufacturer ranges from 40,000 to 50,000, and a significant loss in molecular weight is observed after processing by dialysis in contrast to precipitation (see Figure 4). Due to the processing conditions, a loss in molecular weight is expected due to methacrylation of gelatin, but when further consideration is given to the long suspension of GelMA in aqueous solution at high temperatures, hydrolysis of gelatin occurs during dialysis, resulting in cleavage of peptide bonds, which further reduces the molecular weight (van den Bosch & Gielens, Int J Biol Macromol. 2003, 32(3-5):129-38). Precipitation minimizes the loss in molecular weight, as it eliminates the need for dialysis, and methacrylation is the only major cause of molecular weight loss. From the manufacturer's molecular weight specification of approximately 40 kDa for 175 bloom porcine gelatin (Sigma-Aldrich), dialysis reduced the GelMA weight-average molecular weight to 18.898 ± 0.13 kDa (a 52.76% reduction) compared to the precipitated GelMA weight-average molecular weight of 32.93 ± 0.35 (a 17.67% reduction). The molecular weight of GelMA affects the overall mechanical strength of the hydrogel as demonstrated in the following discussion.

[0064] Compressive strength and swelling ratio One of the inherent properties of a polymer is that its mechanical strength is directly proportional to its molecular weight, and gelatin is in fact rated in terms of its Bloom number. The higher the Bloom number, the higher its molecular weight and the stiffer the gel. The previous results indicate a substantial reduction in molecular weight due to the processes involved in the conversion to GelMA, and the effect of molecular weight reduction is clearly seen in Figure 5b. There was a significant reduction in Young's modulus between DI and PR GelMA, which indeed reflected a substantial molecular weight reduction due to dialysis compared to precipitation. The measurements for 5% DI and PR are 0.7 ± 0.5 and 11.23 ± 1.59 kPa, and for 10% DI and PR, 5.43 ± 1.02 and 19.03 ± 5.5 kPa, respectively. The physical strength is clearly seen in the micrograph in Figure 5a. The swelling ratio, defined as the ratio of the mass of water absorbed to the gel dry mass, was highest at 5% DI, with no significant difference at 5% PR, 10% DI and PR (Figure 5c). In precipitated GelMA, higher mechanical strength can be maintained due to partial maintenance of the molecular weight of gelatin, which is quite useful for tailoring the range of Young's modulus for specific 3D culture conditions.

[0065] Rheological analysis of GelMA hydrogels To evaluate the linear viscoelastic region (LVE) of the synthetic GelMA, strain sweeps were performed and all samples behave linearly up to strain levels between 0.5% and 10% (Figure 6). To confirm the LVE, the storage and loss moduli of GelMA were identified by frequency sweeps (Figure 7). The experimental values ​​obtained for the storage modulus were: 5% DI-14.73 ± 7.96 Pa, 5% PR-135.04 ± 5.95 Pa, 10% DI-734.44 ± 146.85 Pa, 10% PR-1562.2 ± 843.07 Pa, and for the loss modulus, 5% DI-0.87 ± 0.59 Pa, 5% PR-3.37 ± 0.37 Pa, 10% DI-32.04 ± 26.14 Pa, 10% PR-43.23 ± 10.57 Pa. The storage and loss moduli are significantly higher for 10% PR compared to 5% PR and DI, indicating a higher crosslink density due to the molecular weight and polymer concentration of the samples. Time and temperature sweeps (Figures 8 and 9) also indicate the homogeneity and stability of the viscoelastic properties of GelMA. Fluctuations in the loss modulus are evident in a pseudo-steady state trend, but may be due to fluid transport gradients across the hydrogel pores. Stability at T=37°C is essential for the culture conditions, ensuring uniform initial conditions over the time frame of cell culture.

[0066] Biological characterization of hydrogels The cell viabilities on all scaffolds after encapsulation were all above 85% from day 1 onwards, indicating very low or no cytotoxicity after contact with the scaffolds. Focusing on precipitated GelMA and considering that there is no significant difference between the cell viabilities of dialyzed GelMA and precipitated GelMA, this supports previous results that the by-products resulting from the methacrylation of gelatin, i.e., methacrylic acid and unreacted methacrylic anhydride, are substantially removed (Figure 10e). The circular morphology of NIH 3T3 is observed on day 1 of encapsulation, whereas on day 4, cell projections are evident, indicating cell attachment and proliferation. Qualitatively, longer projections were observed at lower concentrations of GelMA (5% DI and PR) which could be attributed to the mechanical strength of the scaffold as evidenced in several papers (Engler, Sen, Sweeney & Discher, Cell 126, 677-689, 2006; Rehfeldt, Engler, Eckhardt, Ahmed & Discher, Advanced Drug Delivery Review, 2007, 59, 1329-1339; Solon, Levental, Sengupta, Georges & Janmey, Biophysical Journal, 2007, 93, 4453-4461).

[0067] The synthesis of GelMA was successful using the downstream processing techniques of dialysis and precipitation. The physical characterization of the product was performed by environmental scanning electron microscopy and thermogravimetric analysis, which showed clear differences in terms of morphology between the powdered precipitated GelMA and the foamed dialyzed GelMA. Qualitatively, the powdered form is much denser, allowing for storage of bulk quantities in a small space. The method significantly reduced the purification time by up to 86% compared to the conventional method. Thermogravimetric analysis showed no significant difference in the salt content of the samples, and further confirmed that the purity in terms of the presence of by-products in the product was comparable between the dialyzed and precipitated GelMA. The degree of methacrylation by TNBS assay was unchanged by both methods. However, the molecular weight was much lower in the dialysis versus the precipitation method, possibly due to hydrolysis of peptide bonds during the duration of dialysis, which significantly affected the overall mechanical strength of the photopolymerized hydrogels. Young's storage and loss moduli confirmed the effect of the molecular weight reduction by compressive and rheological analysis of the hydrogels. A higher range of mechanical strengths is achievable with precipitated GelMA (up to 19 kPa, in contrast to dialyzed GelMA at the same concentration [10%], which is only up to 6 kPa), allowing tuning of the mechanical strength to a large range of values. Finally, the method did not alter cell viability, with a minimum of 85% viability for all encapsulated NIH 3T3 in both precipitated and dialyzed GelMA, further confirming the removal of toxic by-products of gelatin methacrylation by the precipitation method. At day 4, cells in 5% GelMA (DI and PR) have more pronounced cell projections, indicating changes in motility and phenotype compared to 10% GelMA. This is likely due to the porosity and mechanical strength of the hydrogel (Engler et al., 2006; Rehfeldt et al., 2007; Solon et al., 2007), with the lower concentration of GelMA resulting in larger pores and therefore cell motility. Overall, precipitated GelMA can be used as a platform for 3D cell culture operations with mechanical strength values ​​in the higher range compared to dialyzed downstream processing techniques.

[0068] Example 3. Preparation and characterization of alginic acid methacrylate Sodium alginate at 1% wt / vol is dissolved overnight in a pH 9 carbonate-bicarbonate buffer. After dissolution, a 20 molar excess of methacrylic anhydride is added dropwise into the alginate solution. The solution is left stirring for 72 hours before precipitation in 10x reaction volume of denatured ethanol. The precipitate is then collected, washed again in ethanol, and dissolved again in water. The precipitation-washing-dissolution process is repeated 3x, and finally the precipitated alginate methacrylate is freeze-dried overnight. The dried alginate is ground into powder, and using NMR, the degree of methacrylation is 28.82% substitution.

[0069] Example 4. Preparation and characterization of hyaluronic acid methacrylate 1% wt / vol sodium hyaluronate is dissolved overnight in a pH 9 carbonate-bicarbonate buffer. After dissolution, 10 molar excess of methacrylic anhydride is added dropwise into the sodium hyaluronate solution. The solution is left stirring for 12 hours before precipitation in 10x reaction volume of denatured ethanol. The precipitate is then collected, washed again in ethanol, and dissolved again in water. The precipitation-washing-dissolution process is repeated 3x, and the finally precipitated hyaluronic acid methacrylate (HAMA) is freeze-dried overnight. The dried HAMA is ground into powder, and using NMR, the degree of methacrylation is 67.23% substitution.

[0070] The present invention can be further summarized with reference to the following items #1 to #5. #1. Next steps: (1) dissolving a biopolymer in a buffer; (2) adding a chemical modifier; (3) adding a modified biopolymer solution to the precipitation solution for purification; (4) recovering the precipitation solution by distillation; (5) drying to obtain the product. A method for mass-producing modified biopolymers from a raw material by precipitation and drying, comprising: The raw material used is selected from the group consisting of gelatin, alginate, hyaluronic acid, chitosan, chondroitin sulfate, collagen, elastin, cellulose, and silk fibroin; The method produces a product that is a modified biopolymer in the form of a dense powder that can be crosslinked to form hydrogels, nanofibers, and other biomaterials. #2. The buffer solution according to claim 1 is selected from the group consisting of 0.01-0.5M carbonate-bicarbonate buffer, phosphate buffer, organic solvent for polysaccharides, or a mixture thereof. #3. The chemical modifying agent according to claim 1 is selected from the group consisting of methacrylic anhydride, glycidyl methacrylate, and carboxylic anhydride. #4. The precipitation solution used in claim 1 is selected from the group consisting of ethanol, acetone, methanol denatured alcohol, dimethyl sulfoxide, propanol, and chloroform. #5. The drying method of claim 1 is selected from the group consisting of tray drying, freeze drying, conveyor drying, rotary drum drying, or a combination thereof.

Claims

1. Next steps: (a) dissolving a biopolymer selected from proteins, polysaccharides, their salts, and mixtures thereof in an aqueous solution; (b) reacting the biopolymer with a chemical modifying agent containing a carbon-carbon double bond, a carbon-carbon triple bond, and / or a nitrogen-nitrogen triple bond to obtain a solution containing the biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond; (c) adding the solution obtained in step (b) to an organic solvent to obtain a suspension containing a precipitate of the biopolymer chemically modified with the functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond; (d) filtering the suspension obtained in step (c) to obtain the precipitate and a filtrate; (e) distilling the filtrate to recover the organic solvent; and (f) drying the precipitate to obtain the biopolymer chemically modified with the functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond.

1. A method for producing a biopolymer chemically modified with a functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond, comprising:

2. The biopolymer chemically modified with the functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond is a particle, and step (f) is followed by step (g): (g) subjecting the biopolymer obtained in step (f) to a micronization process to prepare particles of the biopolymer; The method of claim 1 further comprising:

3. Step (h) carried out after step (d): dissolving the precipitate in water to obtain a solution containing the biopolymer chemically modified with the functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond; adding the solution to an organic solvent to obtain a suspension containing a precipitate of the biopolymer chemically modified with the functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond; and filtering the suspension to obtain the precipitate and a filtrate. The method of claim 1 further comprising:

4. 2. The method of claim 1, wherein the aqueous solution is selected from an acidic aqueous solution, a basic aqueous solution, and an aqueous buffer solution.

5. The method of claim 1 , wherein the biopolymer comprises at least two biopolymers.

6. The method of claim 1 , wherein the protein is selected from gelatin, collagen, elastin, silk fibroin, albumin, and mixtures thereof.

7. Step (b) comprises the steps of: (b-1) adjusting the pH of the solution to a value between 2 and 10; (b-2) adding the chemical modifying agent to the solution obtained in step (b-1); and (b-3) Stirring at a temperature between room temperature and 60° C. for 0.5 to 5 hours. The method of claim 6, comprising:

8. Step (b) comprises the steps of: (b-4) Stopping the reaction by adjusting the pH of the solution to a value between 6.5 and 7.

5. The method of claim 7, comprising:

9. 2. The method of claim 1, wherein the polysaccharide is selected from alginic acid, gellan gum, pectin, polygalacturonic acid, carrageenan, hyaluronic acid, chitosan, chondroitin sulfate, cellulose, carboxymethylcellulose, hydroxymethylcellulose, glycosaminoglycans, and mixtures thereof.

10. The method of claim 9 , wherein the biopolymer is a polysaccharide salt.

11. Step (b) comprises the steps of: (b-5) adding the chemical modifying agent to the solution obtained in step (a); and (b-6) Stirring for at least 3 hours 10. The method of claim 9, comprising:

12. 2. The method of claim 1, wherein the chemical modifying agent is selected from (meth)acrylic anhydride, glycidyl (meth)acrylate, carbic anhydride, and mixtures thereof.

13. 2. The method of claim 1, wherein the organic solvent is selected from an alcohol, an alcohol-containing composition, a ketone, an ester, an ether, chloroform, and mixtures thereof.

14. 2. The method of claim 1, wherein the drying is selected from tray drying, freeze drying, conveyor drying, rotary drum drying, vacuum drying, and combinations thereof, and / or the pulverization method is selected from grinding, milling, milling, and combinations thereof.

15. A biopolymer chemically modified with functional groups selected from carbon-carbon double bonds, carbon-carbon triple bonds, and nitrogen-nitrogen triple bonds, obtainable by the method of claim 1.

16. Next steps: i) dissolving the biopolymer chemically modified with the functional group selected from a carbon-carbon double bond, a carbon-carbon triple bond, and a nitrogen-nitrogen triple bond according to claim 15 in a solution, and optionally adding a radical initiator to the solution; and ii) cross-linking the biopolymer A hydrogel obtained by a method comprising the steps of: